Comparison of strategies and performance of functional electrical stimulation cycling in spinal cord injury pilots for competition in the first ever CYBATHLON - Christine Azevedo Coste; Vance Bergeron; Rik Berkelmans; Emerson Fachin Martins; Ché Fornusek; Arnin Jetsada; Kenneth J. Hunt; Raymond Tong; Ronald Triolo; Peter Wolf (PAGEPress Publications, 2017)
Functional Electrical Stimulation (FES) can elicit muscular contraction and restore motor function in paralyzed limbs. FES is a rehabilitation technique applied to various sensorimotor deficiencies and in different functional situations, e.g. grasping, walking, standing, transfer, cycling and rowing. FES can be combined with mechanical devices. FES-assisted cycling is mainly used in clinical environments for training sessions on cycle ergometers, but it has also been adapted for mobile devices, usually tricycles. In October 2016, twelve teams participated in the CYBATHLON competition in the FES-cycling discipline for persons with motor-complete spinal cord injury. It was the first event of this kind and a wide variety of strategies, techniques and designs were employed by the different teams in the competition. The approaches of the teams are detailed in this special issue. We hope that the knowledge contained herein, together with recent positive results of FES for denervated degenerating muscles, will provide a solid basis to encourage improvements in FES equipment and open new opportunities for many patients in need of safe and effective FES management. We hope to see further developments and/or the benefit of new training strategies at future FES competitions, e.g. at the Cybathlon 2020 (www.cybathlon.ethz.ch).